(3GdJCgjd GdGLJeGYj dCSQI SLjf GdCNP HGdKCQ ef efXhQ NOeI GdaQO (B/s - (3ehSi, ehSi fLjHs ((3GdEScfOQjI (B[(3eUQ(B] :s (3GdecJH GdLGeYj GdMOjK,s, 2020)
(3gPG GdcJGH (B"(3GdJCgjd GdGLJeGYj dCSQI SLjf GdCNP HGdKCQ(B"(3, GdCNP HGdKCQ XGgQI bOjeI heJLPQI aj eLJeY UYjO eUQ, haj GdCYQGa hGdYGOGJ hGdJbGdjO GdJj JSjQ TDhf GdMjGI ajg, Hd JMhdJ Edi feW MjGI eJcGed efP eFGJ GdSfjf, hKbGaI GLJeGYjI dG jLhR GdJfGRd YfgG Hjf GdYOjO ef GdYGFdGJ, hQZe Pdc agh jfXQ Edjg ef hLgI GdfXQ GdbGfhfjI Ydi Cfg LQjeI bJd YeO hjJYGed GdbGJd habG dCMcGe bGfhf GdELQGAGJ GdLfGFjI aj eKd gPg GdMGdGJ(B.s
(3jTJed Ydi edGMb(B.s
(3eTJQjGJ eYQV GdbGgQI GdOhdj ddcJGH (B2020.s
(3HHdjhLQGajI (B: (3UaMI (B453-478.s
Keywords: (3GdNOeI GdGLJeGYjI ddeLQejfs; (3GdeSLhfhfs -- (3EYGOI JCgjds